Construction of an Indonesian Biographical Novel: Based on Reader Reception of Buya Hamka’s Biographical Novel - Abimubarok, Achmad; Hikmat, Ade; Suryoputro, Gunawan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Research on biographical novels is mostly focused on how novelists represent figures as protagonists, but they have not explored what the contents of the novel would be like if they used the same figure. In addition, there is no research that constructs the characteristics of biographical novels in Indonesia. This study aims to answer the assumption whether biographical novels present different characteristics even though they emanate from the same figure. Through the Buya Hamka’s biographical novel, this study also leads the efforts to delineate the characteristics of the biographical novel in Indonesia. In order to obtain more objective evidence and constructs, readers’ reception is used as an analytical perspective. In addition, netnography is adopted as a research method because the utilized data comes from social networks. Netnography is expected to facilitate more structured reception results. Our results show that biographical novels still present different characteristics even though they use the same figure. The logical assumption related to these differences is that the novel has a fictitious nature and the novelist has a creative way of interpreting figures as protagonists. This proof also conveys that the characteristics of biographical novels are closely related to their figures/protagonists; the figure as the protagonist, the historical content as the context of the event, the protagonist who is inspiring, the events that are attached to the protagonist, and the style of writing as the personal representation of the protagonist. Through these characteristics, it is possible to distinguish between biographical novels and other novels, including historical novels.Keywords: Biographical Novels; Buya Hamka; Reader’s Reception; Indonesian Literature